Body Mass Index, Diabetes and Intrahepatic Cholangiocarcinoma Risk: The Liver Cancer Pooling Project and Meta-analysis - Petrick, Jessica L; Thistle, Jake E; Zeleniuch-Jacquotte, Anne; Zhang, Xuehong; Wactawski-Wende, Jean; Van Dyke, Alison L; Stampfer, Meir J; Sinha, Rashmi; Sesso, Howard D; Schairer, Catherine; Rosenberg, Lynn; Rohan, Thomas E; et al. (The American journal of gastroenterology, 2018)
Obesity and diabetes are associated with an increased liver cancer risk. However, most studies have examined all primary liver cancers or hepatocellular carcinoma, with few studies evaluating intrahepatic cholangiocarcinoma (ICC), the second most common type of liver cancer. Thus, we examined the association between obesity and diabetes and ICC risk in a pooled analysis and conducted a systematic review/meta-analysis of the literature. For the pooled analysis, we utilized the Liver Cancer Pooling Project, a consortium of 13 US-based, prospective cohort studies with data from 1,541,143 individuals (ICC cases n = 414). In our systematic review, we identified 14 additional studies. We then conducted a meta-analysis, combining the results from LCPP with results from the 5 prospective studies identified through September 2017. In the LCPP, obesity and diabetes were associated with a 62% [Hazard Ratio (HR) = 1.62, 95% Confidence Interval (CI): 1.24-2.12] and an 81% (HR = 1.81, 95% CI: 1.33-2.46) increased ICC risk, respectively. In the meta-analysis of prospectively ascertained cohorts and nested case-control studies, obesity was associated with a 49% increased ICC risk [Relative Risk (RR) = 1.49, 95% CI: 1.32-1.70; n = 4 studies; I = 0%]. Diabetes was associated with a 53% increased ICC risk (RR = 1.53, 95% CI: 1.31-1.78; n = 6 studies). While we noted heterogeneity between studies (I = 67%) for diabetes, results were consistent in subgroup analyses. Results from hospital-based case-control studies (n = 9) were mostly consistent, but these studies are potentially subject to reverse causation. These findings suggest that obesity and diabetes are associated with increased ICC risk, highlighting similar etiologies of hepatocellular carcinoma and intrahepatic cholangiocarcinoma. However, additional prospective studies are needed to verify these associations.